Morphological and molecular characterisation of Strongyloides ransomi (Nematoda: Strongyloididae) collected from domestic pigs in Bac Giang province, Vietnam - Huong Giang, Nguyen Thi; Hoan, Tran Duc; Thu Huyen, Nguyen Thi; Kim Lan, Nguyen Thi; Doanh, Pham Ngoc (Academia Journal of Biology, 2017)
The genus Strongyloides is a group of parasitic nematodes of vertebrates comprised of over 50 species. A large numbers of nucleotide sequences of Strongyloides species have been deposited in GenBank. The vast majority of them are of Strongyloides from human beings, non-human primates, rats and cattle, but there are few molecular data of Strongyloides species isolated from pigs. The aim of this study is to identify Strongyloides species collected from pigs from Bac Giang Province, Vietnam, and analyze their molecular phylogenetic relationship within the genus Strongyloides based on 18S rDNA sequences. The morphological and molecular analyses revealed that the Strongyloides samples collected from pigs from Bac Giang Province, Vietnam, were in fact S. ransomi. The 18S rDNA sequences of S. ransomi from Vietnam were completely identical with that from Cambodia, but slightly different (0.3%) from that of Japan. In comparison to other Strongyloides species, S. ransomi was genetically close to S. venezuelensis. Citation: Nguyen Thi Giang, Tran Duc Hoan, Nguyen Thi Thu Huyen, Nguyen Thi Kim Lan, Phạm Ngọc Doanh, 2017. Morphological and molecular characterisation of Strongyloides ransomi (Nematoda: Strongyloididae) collected from domestic pigs in Bac Giang province, Vietnam. Tap chi Sinh hoc, 39(3): 270- 275. DOI: 10.15625/0866-7160/v39n3.10796. *Corresponding author: pndoanh@yahoo.com Received 18 May 2017, accepted 20 August 2017